ANALISIS FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGE KERJA WANITA SEKOR FORMAL DI PROVINSI NUSA TENGGARA BARAT 2019-2021 - Rozzy Aprirachman (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
This study aims to identify the factors that influence the absorption of female workers in the formal sector, the factors that affect the absorption of female workers are used as independent variables while the absorption of female workers is the dependent variable. This research attempts to look at the effect of education, working hours, and the status of married women on the absorption of female workers in the formal sector from ten urban districts in the province of West Nusa Tenggara from 2019-2021. This study uses secondary data sourced from the Central Bureau of Statistics (BPS) of West Nusa Tenggara province. The analytical tool used is panel data regression with the Fixed Effect Model (FEM). The results of this study are education has a positive and significant effect on the absorption of female workers in the formal sector of 0.3240401 units, the working hours variable has a positive but not significant effect of 0.0057071 units, while the status of married women has a negative effect on the absorption of female workers in the formal sector of 6.59833 units